Is VAT Administration System Efficient? The Case of the Czech - Hana Zídková; Tomáš Vrána (Central European Public Administration Review)
This paper is focused on the efficiency of VAT collection under the standard credit invoice method. It discusses several approaches on how to evaluate the efficiency of the VAT system. The authors create their own indicator called the C-Coefficient that determines how many times must one unit of currency be checked by the financial authority to collect it into public budgets. The C-Coefficient is calculated from the data on VAT revenues and total VAT paid on all taxable supplies performed in the economy. The concrete results are shown for the Czech Republic for the period 2005 to 2018. The C-Coefficient reaches the values between 7.92 and 11.56, meaning that in the most efficient year (2018) the tax authorities had to inspect each collected CZK more than 7 times, whereas in the least efficient year (2008) they had to audit each collected CZK more than 11 times. Authors also discuss what influences the C-Coefficient. Among important factors are measures against VAT fraud, especially the specific reverse charge, as well as the number of VAT payers in the production and distribution chain and the difference between the average VAT rates applicable on final and intermediate consumption.